Allicin: A review of its important pharmacological activities - Vivek D. Savairam; Neha A. Patil; Shrikant R. Borate; Mahesh M. Ghaisas; Rajkumar V. Shete (Elsevier, 2023)
Background: Garlic (Allium sativum L.) is known for its synthesis of allicin, a defense molecule that exhibits various biological activities. Traditional medicine has utilized garlic to alleviate multiple ailments due to its broad spectrum of effects. Objective: This study aimed to review the ethnomedicinal potentials and pharmacological activities of allicin, the active constituent of garlic. Method: A comprehensive review was conducted to analyze in vitro and in vivo studies on allicin. The focus was on investigating its diverse pharmacological properties, including neuroprotection, anti-alzheimer, anti-inflammatory, anticancer, antioxidant, cardio protective, antidiabetic, and hepatoprotection activity. Results: The review revealed that allicin possesses a range of pharmacological activities. It showed neuroprotective effects, exhibited anti-inflammatory properties, demonstrated anticancer activity, acted as an antioxidant, provided cardioprotection, exerted antidiabetic effects, and offered hepatoprotection. Conclusion: The findings of this study suggest that allicin holds great potential for pharmaceutical industries in developing therapeutic products. However, to ensure the safe and effective use of allicin for treating various diseases, further research is necessary. Human clinical trials and quality control studies are essential to establish appropriate doses for pharmaceutical applications.